2020
DOI: 10.1101/2020.03.25.008342
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Global computational alignment of tumor and cell line transcriptional profiles

Abstract: Cell lines are key tools for preclinical cancer research, but it remains unclear how well they represent patient tumor samples. Identifying cell line models that best represent the features of particular tumor samples, as well as tumor types that lack in vitro model representation, remain important challenges. Gene expression has been shown to provide rich information that can be used to identify tumor subtypes, as well as predict the genetic dependencies and chemical vulnerabilities of cell lines. However, di… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
54
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(61 citation statements)
references
References 76 publications
(90 reference statements)
6
54
1
Order By: Relevance
“…We observed that primary tumors cluster together based on their tissue type ( Figure 3 C). Cell lines, however, show different behaviors – most do cluster with the tumors from a similar tissue of origin, while a group of cell lines cluster together and away from the tumors, regardless of their tissue of origin, as observed in previous studies 43 . To quantify the degree of co-clustering of cell lines and tumors, we compared distances between tumors and cell lines from similar and non-similar tissues, and observed, as expected, a higher similarity between tumors and cell lines from the same tissue ( Supp Figure 10 C).…”
Section: Resultssupporting
confidence: 68%
“…We observed that primary tumors cluster together based on their tissue type ( Figure 3 C). Cell lines, however, show different behaviors – most do cluster with the tumors from a similar tissue of origin, while a group of cell lines cluster together and away from the tumors, regardless of their tissue of origin, as observed in previous studies 43 . To quantify the degree of co-clustering of cell lines and tumors, we compared distances between tumors and cell lines from similar and non-similar tissues, and observed, as expected, a higher similarity between tumors and cell lines from the same tissue ( Supp Figure 10 C).…”
Section: Resultssupporting
confidence: 68%
“…In the single-cell domain, bindSC can clearly be applied to align cells and features simultaneously, which are important for ongoing investigations in the Human Cell Atlas 43 , the NIH HubMap 44 , the Human Tumor Cell Network 45 and on remodeling of tumor microenvironment 46 . Further, bindSC can potentially be applied to other domains, such as integrating patient sample mRNA profiles with cell-line drug-sensitivity data 47 .…”
Section: Integrating Single-cell Rna With Protein Datamentioning
confidence: 99%
“…In the single-cell domain, bindSC can clearly be applied to align cells and features simultaneously, which are important for ongoing investigations in the Human Cell Atlas 43 , the NIH HubMap 44 , the Human Tumor Cell Network 45 and on remodeling of tumor microenvironment 46 . Further, bindSC can potentially be applied to other domains, such as integrating patient sample mRNA profiles with cell-line drug-sensitivity data 47 .…”
Section: Integrating Single-cell Rna With Protein Datamentioning
confidence: 99%